2011
DOI: 10.1103/physreva.84.063639
|View full text |Cite
|
Sign up to set email alerts
|

d-wave superfluidity in optical lattices of ultracold polar molecules

Abstract: Recent work on ultracold polar molecules, governed by a generalization of the t-J Hamiltonian, suggests that molecules may be better suited than atoms for studying d-wave superfluidity due to stronger interactions and larger tunability of the system. We compute the phase diagram for polar molecules in a checkerboard lattice consisting of weakly coupled square plaquettes. In the simplest experimentally realizable case where there is only tunneling and an XX-type spin-spin interaction, we identify the parameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 73 publications
(177 reference statements)
1
19
0
Order By: Relevance
“…[490] predicted a ferroelectric phase, arising due to dipole-dipole interactions in an ensemble of ultracold polar molecules. [491] have shown that molecules can realize d−wave superfluid phases. [492] proposed a technique to prepare spin crystals of ultracold molecules non-adiabatically, bypassing the usual Kibble-Zurek scaling.…”
Section: Quantum Simulation With Rotational States In Dipolar Gasesmentioning
confidence: 99%
“…[490] predicted a ferroelectric phase, arising due to dipole-dipole interactions in an ensemble of ultracold polar molecules. [491] have shown that molecules can realize d−wave superfluid phases. [492] proposed a technique to prepare spin crystals of ultracold molecules non-adiabatically, bypassing the usual Kibble-Zurek scaling.…”
Section: Quantum Simulation With Rotational States In Dipolar Gasesmentioning
confidence: 99%
“…Second, and perhaps more importantly, the anisotropic and long-range nature of the interaction allows for the realization of novel quantum phases, especially when the spatial dimensions of the system can be varied with optical lattices. Some of these engineered systems may find relevance to outstanding problems in condensed-matter physics [13,14]; moreover, qualitatively new types of physics can emerge in the presence of long-range interactions [15,16,17,18,19,20,21]. As a specific example of a unique feature of long-range interactions, a spin-1/2 Hamiltonian can be encoded based on a pair of oppositeparity rotational states where dipolar interactions give rise to a direct spin exchange coupling between molecules [22,23].…”
mentioning
confidence: 99%
“…Having obtained a matrix representation of the symmetry operatorsP R on the particle number sector (N ↑ , N ↓ ), we can decompose this subspace of Hilbert space further into the irreducible invariant subspaces of D 4 via the projection operator technique 42 (see also 40 for a detailed discussion). In the decomposition of a reducible representation the n-th irreducible representation occurs a n times, given by 42…”
Section: Acknowledgmentsmentioning
confidence: 99%